Pengaruh Brand Image dan Kualitas Produk Terhadap Keputusan Pembelian Minuman Esteh Indonesia di Kecamatan Kedamean Kabupaten Gresik - Idayani Agustina; Is Fadhilah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The beverage industry is becoming increasingly competitive, making it crucial for businesses to establish a strong brand image and product quality to attract consumers. This study aims to analyze the influence of brand image and product quality on purchase decisions for Esteh Indonesia drinks. A quantitative research method was employed, untilizing non-probability sampling techniques. Data was collected through questionnaires distributed to 50 respondets in Kedamean District, Gresik Regency. Multiple linear regression analyseswas used as the data analysis technique. The findings revealed that brabd image has a positive impact on purchase influence, while product quality does not have a significant positive impact on purchase decisions for Esteh Indonesia drinks. However, the influence of brand images was found to be stronger than that of product quality. These findings suggest that Esteh Indonesia should maintain its brand image and enhance product quality to reinforce consumer purchase decisions. additionally, Esteh Indonesia should cultivate a positive brand image through various marketing strategies to enchance brand appeal among costumers.